2019
DOI: 10.3389/fpsyg.2019.02349
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of Residents’ Pro-tourism Behavioral Intention: Place Image, Place Attachment, and Attitude

Abstract: Few prior studies have investigated place image from the residents’ perspective, how this and residents’ place attachment influence attitude to tourism, and consequent reactions. Accordingly, this study aims to develop a model for local residents’ pro-tourism behavioral intention and to discover the relationships between constructs. Analysis was based on a sample of 370 residents in Huangshan City, China. Results indicate that residents’ attitude to tourism positively affects their pro-tourism behavioral inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 82 publications
(153 reference statements)
4
47
1
Order By: Relevance
“…Han et al (2019) also found that PA was significantly and positively associated with attitude in a sample of festival attendees in Cheongsando, South Korea. Likewise, Shen et al (2019) revealed that residents’ PA positively affected their attitudes towards tourism and pro-tourism behavioural intention. Conducting research in the Xuefeng Mountain Area, China, Hu et al (2019) found that PA was positively related to residents’ pro-tourism behaviours.…”
Section: Literature Reviewmentioning
confidence: 96%
See 2 more Smart Citations
“…Han et al (2019) also found that PA was significantly and positively associated with attitude in a sample of festival attendees in Cheongsando, South Korea. Likewise, Shen et al (2019) revealed that residents’ PA positively affected their attitudes towards tourism and pro-tourism behavioural intention. Conducting research in the Xuefeng Mountain Area, China, Hu et al (2019) found that PA was positively related to residents’ pro-tourism behaviours.…”
Section: Literature Reviewmentioning
confidence: 96%
“…In the theoretical studies, social exchange theory is the most preferred framework for investigating residents’ attitudes towards tourism development, followed by social representation theory, institutional theory and bottom-up spillover theory (Hadinejad et al , 2019). Overall, whether atheoretical or theoretical, the main purpose of these studies on residents’ BI was to explore the influencing factors, including attitudes towards tourism (Martín et al , 2017; Shen et al , 2019; Ribeiro et al , 2017), perceived impacts (Hammad et al , 2017; Nazneen et al , 2019; Papastathopoulos et al , 2019), local economy and personal benefit (Garau-Vadell et al , 2019; Ribeiro et al , 2017), community satisfaction (Gursoy et al , 2019), emotion (Zheng et al , 2019), image (Kang, 2019) and community participation (Boonsiritomachai and Phonthanukitithaworn, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the imbalance of social development in ethnic villages, the villagers seem to be in a disadvantaged position ( Li et al, 2016 ). A series of problems such as low participation enthusiasm and frequency of residents occurs in the process of tourism poverty alleviation in ethnic villages, leading to a strange circle of “more help, more poverty.” The participation of residents is related to the sustainable development of tourism ( Murphy, 1988 ; Sharpley, 2014 ; Khalid et al, 2019 ; Shen et al, 2019 ) and the vital interests of residents ( Hwang et al, 2012 ). During the critical period of China to eradicate absolute poverty and secure a decisive victory in building a moderately prosperous society in all respects, how to inspire ethnic village residents to participate in tourism poverty alleviation and improve the quality and effectiveness of tourism poverty alleviation has become an urgent issue for industry and academia ( Yang, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Without communication, there will be no community; conversely, without community, there will be no communication (Zeng et al, 2017). As the stakeholders, tourists, and local residents are becoming increasingly important in tourism destinations (Shen et al, 2019), their support is seen as an important prerequisite for the sustainability of tourism in destinations (Sinclair-Maragh and Gursoy, 2016;Ribeiro et al, 2017). In this study, the experience of an intangible cultural heritage exhibition is a participatory narrative experience based on community cultural ecology.…”
Section: Cultural Tourism and Intangible Cultural Heritagementioning
confidence: 98%